Acne vulgaris in Saudi Arabia: A systematic review - Aishah Zayed J. Alanazi (Wolters Kluwer Medknow Publications, 2020)
Introduction: Acne vulgaris (AV) is one of the most common dermatological disorders. However, data of AV in Saudi Arabia are not well documented. Purpose: To determine the prevalence, potential risk factors, psychological impact, and treatment modality of AV in the Kingdom of Saudi Arabia and highlights the gaps of knowledge related to this disease. Methods: The literature search was performed using the keywords "acne vulgaris," "Saudi Arabia," and "KSA" in four electronic databases: PubMed, Google Scholar, Web of Science, and Embase. The search was restricted by the locational filter of Saudi Arabia and a timeframe of 2010-2019. Results: 453 potentially relevant titles and abstracts being identified, of which 18 articles met the inclusion criteria. AV is becoming more prevalent among the Saudi population, particularly among Saudi women. The knowledge and awareness of the public is relatively low. Conclusion: Community-based interventions on acne are needed to increase the awareness and to improve the perception and belief of acne patients. Further studies are needed to evaluate the effects and side effects of different complementary medicine and over-the-counter modalities.